PEMIKIRAN NASHIRUDDIN AL-THUSI TENTANG EKONOMI - Siti Fauziyah; Ali Samsuri (Al-Iqtishad: Jurnal Ekonomi Syariah, 2024)
Abstract Nasruddin Tusi's economic thought represents a significant contribution to the development of medieval Islamic economic thought. In his renowned work, "Akhl??q-i N?????ir??" (Nasirian Ethics), Tusi elaborates his views on how Islamic societies should manage their economic affairs. One of the key concepts he advances is social justice, where Tusi emphasizes the importance of fair distribution of wealth and resources within society. Additionally, Tusi highlights the role of education in economic development and social progress, believing that higher levels of education can help alleviate poverty and foster innovation. Furthermore, Tusi considers the role of the state in managing the economy for the common good, underscoring the importance of economic stability in creating a conducive environment for economic growth and societal well-being. This paper aims to summarize Nasruddin Tusi's economic thought and its implications in the context of medieval Islamic society and its relevance in contemporary economic thought. By delving into Tusi's ideas, we can gain valuable insights into how classical Islamic concepts can be applied to understand and address modern economic challenges.